Unpacking gender-based violence in sport: How can the sport sector effectively respond to the need for safe sporting contexts? - Hayley Truskewycz (Current Issues in Sport Science)
This symposium proposes to illustrate three pertinent elements of the ongoing process of knowledge creation, analysis and transfer in the field of safe sport. The first presentation introduces an empirical study of the diffusion of terminology and practical policy at the level of international sport federations. The results highlight how implementation of policy around the sensitive and ethically laden issue of safeguarding is often performative at this level of sport governance. The second presentation questions how knowledge produced prevalence studies on abuse in sport is created, how it is used and by whom. The multi-method research unveils fervently political and personally beneficial motivations for studies that produce results showing high rates of abuse. The final presentation details the Global Observatory for Gender Equality & Sport as an organisation situated between academia and practitioners tasked with knowledge collation and diffusion. Explaining the organisation’s operation in this space illustrates the challenges and opportunities for knowledge transfer, and offers 4S researchers a chance to broaden the reach of their work.